(379) التخطيط على مستوى الوحدة Unit-level planning - فتحى الحسينى خليل (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة مفهوم "التخطيط على مستوى الوحدة" (المصنع أو المزرعة) وعلاقته بالتخطيط القومي الشامل، حيث تستعرض الوحدة الاقتصادية باعتبارها المستوى التخطيطي الأول وقاعدة الهرم التي تمد الدولة بالبيانات الدقيقة ويبين البحث أن نجاح التخطيط يتطلب دمج الأهداف الخاصة للوحدة مع الأهداف التنموية للمجتمع، مع ضرورة إعداد خطط تفصيلية تغطي مجالات الإنتاج، ومستلزمات الإنتاج، والعمالة، والتكاليف، وتسويق المنتجات لضمان الكفاءة الاقتصادية ، كما تركز الملف على الجانب التقني لاتخاذ القرارات باستخدام "أسلوب البرمجة الخطية" كأداة رياضية للوصول إلى "الحل الأمثل" الذي يحقق أقصى ربح أو أدنى تكلفة في ظل الموارد المتاحة ويقدم البحث نماذج تطبيقية واقعية لمشكلات معقدة، مثل تحديد المزيج الإنتاجي الأمثل لشركات البلاستيك، وحل مشكلات النقل لشركات النسيج من خلال مصفوفات التكاليف، مؤكداً على أن استخدام الحاسبات الإلكترونية والأساليب الرياضية الحديثة هو السبيل العلمي لتطوير الإدارة وتجنب القرارات العشوائية. This memorandum addresses the concept of "unit-level planning" (factory or farm) and its relationship to comprehensive national planning. It examines the economic unit as the first planning level and the base of the pyramid, providing the state with accurate data. The research demonstrates that successful planning requires integrating the unit's specific objectives with the developmental goals of society. It also highlights the necessity of preparing detailed plans covering production areas, production inputs, labor, costs, and product marketing to ensure economic efficiency. Furthermore, the memorandum focuses on the technical aspects of decision-making, employing "linear programming" as a mathematical tool to arrive at the "optimal solution" that achieves maximum profit or minimum cost within available resources. The research presents real-world case studies of complex problems, such as determining the optimal production mix for plastics companies and solving transportation problems for textile companies using cost matrices. It emphasizes that using computers and modern mathematical methods is the scientific approach to developing management and avoiding arbitrary decisions.